Comparative Study of Quality of Life and Obsessive-Compulsive Tendencies in Patients With Chronic Hand Eczema and Lichen Simplex Chronicus. Issue 3 (May 2016) - Kouris, Anargyros; Christodoulou, Christos; Efstathiou, Vasiliki; Platsidaki, Eftychia; Tsatovidou, Revekka; Torlidi-Kordera, Evangelia; Rigopoulos, Dimitrios; Kontochristopoulos, George
Abstract : Background: Lichen simplex chronicus (LSC) and chronic hand eczema (CHE) are 2 common dermatological disorders that affect physical, social, and psychological aspects of life. The aim of this study was to compare quality of life and obsessive-compulsive tendencies between patients with LSC and patients with CHE. Materials and Methods: Sixty patients with LSC, 60 patients with CHE, and 60 healthy controls were included in the study. Quality of life was evaluated according to the Dermatology Life Quality Index (DLQI). Patients were also assessed for compulsive behavior with the Leyton Trait Scale. Results: Patients with LSC (13.00 [1.41]) had a statistically significant higher mean (SD) DLQI compared with patients with CHE (11.33 [1.53]). Patients with LSC (13.97 [2.14]) presented statistically significant higher levels of obsessive-compulsive personality traits than patients with CHE (12.48 [2.69]), whereas both groups also differed from the healthy controls (10.68 [3.87]). The DLQI was not correlated with the Leyton Trait Scale in either the patients with LSC (r = 0.10, P = 0.50, not significant [NS]) or in the CHE patients (r = 0.01, P = 0.92, NS). Conclusions: Although both LSC and CHE are associated with impaired quality of life and obsessive-compulsive tendencies, significantly higher scores were recorded in patients with LSC.